Pengaruh Model Project Based Learning (Pjbl) Terhadap Hasil Belajar IPA Materi Pokok Makhluk Hidup dan Lingkungan - Sumampow, Zoya F.; Najoan, Roeth; Lantang, Elisabeth; Kanal, Vani (Peneliti.net, 2023)
The aims of this research are to (1) determine the impact of the project-based learning model (PjBL); The results of students' science learning which is material about living things and the environment in class V of Pineleng State Elementary School. (2) knowledge of the impact of the project-based learning model (PjBL) on the value of project results; Create a binary classification table and determine keys for class V of Pineleng State Elementary School. This research uses a quantitative type of research. The subjects of this research used two experimental classes, namely Class V B as Experiment Class 1 and Class V A as Control Class. The experimental class displays a project-based learning model. The control class uses a traditional learning model according to the teacher's lesson plan. In this research, data taken in three ways, namely observation, tests, and project assessment. Data analysis techniques use validity tests, reliability tests, homogeneity tests, normality tests, and one-way Anova tests. Based on the results of the analysis of teacher activity observations, it was obtained 0.95, which means very strong, while the results of the analysis of student activity observations were obtained 0.9, which means very strong, meaning that the results of observing teacher and student activities were classified in the very strong category. Meanwhile, the results of the one-way Anova test calculation obtained fcount= 210.64 < ftabel= 3.09, so ho (null hypothesis) is rejected and ha (alternative hypothesis) is accepted, meaning there is a significant influence on the Project Based Learning model on learning outcomes in creature material. life and environment. Then, for the results of the student project assessment, experimental class 1 obtained a high average score with a score of 79. This means that the following score is that experimental class 1 meets the KKM according to the project-based learning model.